Medical competencies in palliative care for internal medicine residency - Araújo, Manuel Bernardo Clemente Figueira (2021)
Objective: The objective of this review is to list the basic palliative competencies that should be acquired throughout the internal medicine residency program in Portugal. Introduction: Palliative care and the relief of suffering were described as the most neglected dimensions in public health in 2018 and the aging of the population is leading to an increase of chronic diseases. Being the main focus of internists, these are required to develop basic competencies in palliative care in order to assure universal palliative care access. In Portugal the Internal Medicine specialist curriculum is absent regarding palliative care competencies. Methods: This scoping review is based on JBI methodology. The search was conducted in December 2019. Inclusion Criteria: studies published in international data bases and grey literature in English, Spanish, French and Portuguese languages with no time limit with a clear description of competencies formulated for the internal medicine specialty. Results: A total of 5032 records from international databases and 15 from grey literature were obtained for analysis. From these 31 articles were included in this review. A total of 1064 competencies were listed from there documents. These competencies were sorted according to 7 domains: 1 Clinical competencies; 2 Psychosocial Issues; 3 Ethical, Legal aspects and Professionalism competencies; 4 Communication competencies; 5 Teamwork competencies; 6 health system network related competencies; 7 Competencies in Education and Evidence Based Medicine. After sorting and simplifying the listing, we obtained a total of 248 competencies. Conclusion: Internal medicine physicians provide palliative care to patients in their daily practice and have done so since ever. Whether one pursues specialization or not, all internists can, and should use, the growing knowledge of palliative medicine in their medical practice. With the data from this scope we hope to provide a tool that allows the elaboration of a formal curriculum for the internal medicine specialty.